Hub-and-spoke network design for liner shipping - Guo, Hao (2016)
For the purpose of cutting operating cost, more large vessels are built and deployed by liner shipping companies. The Hub and Spoke (H&S) network is commonly used in transportation industry to reduce total cost by consolidation in the hub ports. The H&S network design has attracted much attention and a lot of related work can be found in road and aviation industry. However, there are few papers focusing on the liner shipping industry. Moreover, in many liner shipping companies, the H&S network is designed mainly by experienced employees or by industry practice. A Mixed-Integer Linear Programming (MIP) is proposed to facilitate liner companies to make the decision. It addresses how to design an H&S network from just a set of ports. The main objective is to maximize the profit derived from the whole network. Some related constraints are made in respect to the limitation on fleet size, transit time, containers flow and so on. In this article, a possible solution method is also suggested to make the solving process more efficient.